The EFFECTIVENESS OF USING GOOGLE TRANSLATE AS A TOOL FOR ASSISTING STUDENTS IN DOING EXERCISES IN ENGLISH SUBJECT CLASSROOM - Desty Febria; Zephanya Ruth Gabriella (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research was conducted to find out whether Google Translate is effective or not in assisting students doing their exercises in English subject classroom. The method used was Classroom Action Research (CAR). The population of this research was the 31 active students of XI MIPA class in one of Batam's private senior high school; SMA Kartini Batam. Before conducting a thorough research, an observation was conducted in order to understand the students' behaviour and their opinions regarding the use of gadget and Google Translate in English subject classroom. Afterwards, students were given a pre-test in a form of exercise for their English class. They were not allowed to use anything in working on their exercise. The required score was 77 to be marked as pass. The total mean score was 81.9 for the pre-test. It can be concluded that they are still knowledgeable even though they were not utilizing the machine translation. After reviewing and giving feedback to the students, the post-test was commenced with 92.9 as the result. It can be said that the use of Google Translate in assisting students doing their exercises in English subject classroom is effective and enhanced students' knowledge.